RESPON PERTUMBUHAN DAN HASIL TOMAT CERI PADA BERBAGAI MEDIA TANAM DI LAHAN HOLTIKULTURA, GRESIK - Haikal, Muhammad Fikri; Wiharyanti Nur Lailiyah (Universitas Medan Area, 2023)
Cherry tomatoes (Solanum Lycopersium Mill) are horticultural crops that are rich in vitamins A and C. Cherry tomatoes are one of the prospective agricultural products in Indonesia and have a higher economic value. Planting media is defined as a place where plants live according to their life requirements. The combination of growing media has an effect on the growth and yield of cherry tomato plants. Charcoal husks or roasted husk charcoal can be used as a planting medium and has light characteristics, namely 0.2 kg per liter of rice, coarse texture so it has high air circulation. Besides charcoal, goat manure husks can also be used as a mixture of planting media. Goat manure contains nitrogen nutrients which are useful during plant growth. The aim of this study was to examine the response and differences in media treatment on the growth of cherry tomatoes. This study used a single factor Completely Randomized Design (CRD) with Goat Manure, Husk and soil as the medium which resulted in 7 treatments. Each treatment was repeated four (4) times, so that 28 experimental units were obtained, there were 224 plants. Obtained observational data will be analyzed using Analysis of Variance (Anova). If there is a significant difference, it will be continued with the 5% BNT Advanced Test. The results showed that there was no significant difference in the application of various growing media on the growth and yield of cherry tomato plants.